Primeval very low-mass stars and brown dwarfs – VI. Population properties of metal-poor degenerate brown dwarfs. Issue 1 (14th March 2019) - Zhang (张曾华), Z H; Burgasser, A J; Gálvez-Ortiz, M C; Lodieu, N; Zapatero Osorio, M R; Pinfield, D J; Allard, F
ABSTRACT: We presented 15 new T dwarfs that were selected from UKIRT Infrared Deep Sky Survey, Visible and Infrared Survey Telescope for Astronomy , and Wide-field Infrared Survey Explorer surveys, and confirmed with optical to near-infrared spectra obtained with the Very Large Telescope and the Gran Telescopio Canarias. One of these new T dwarfs is mildly metal-poor with slightly suppressed K -band flux. We presented a new X-shooter spectrum of a known benchmark sdT5.5 subdwarf, HIP 73786B. To better understand observational properties of brown dwarfs, we discussed transition zones (mass ranges) with low-rate hydrogen, lithium, and deuterium burning in brown dwarf population. The hydrogen burning transition zone is also the substellar transition zone that separates very low-mass stars, transitional, and degenerate brown dwarfs. Transitional brown dwarfs have been discussed in previous works of the Primeval series. Degenerate brown dwarfs without hydrogen fusion are the majority of brown dwarfs. Metal-poor degenerate brown dwarfs of the Galactic thick disc and halo have become T5+ subdwarfs. We selected 41 T5+ subdwarfs from the literature by their suppressed K -band flux. We studied the spectral-type–colour correlations, spectral-type–absolute magnitude correlations, colour–colour plots, and HR diagrams of T5+ subdwarfs, in comparison to these of L–T dwarfs and L subdwarfs. We discussed the T5+ subdwarf discovery capability of deep sky surveys in the 2020s.